2010
DOI: 10.1111/j.1365-2966.2010.16442.x
|View full text |Cite
|
Sign up to set email alerts
|

The host galaxies of core-collapse supernovae and gamma-ray bursts

Abstract: We present a comparative study of the galactic and small‐scale environments of gamma‐ray bursts (GRBs) and core‐collapse supernovae (CCSNe). We use a sample of 34 GRB hosts at z < 1.2, and a comparison sample of 58 supernova hosts located within the Great Observatories Origins Deep Survey footprint. We fit template spectra to the available photometric data, which span the range 0.45–24 μm, and extract absolute magnitudes, stellar masses and star formation rates from the resulting fits. Our results broadly corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
306
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(327 citation statements)
references
References 83 publications
(131 reference statements)
20
306
0
1
Order By: Relevance
“…Long-duration GRBs are typically associated with the peak light in their host galaxies, and with recent star formation (e.g Svensson et al 2010). However, the broadband continuum emission of the host of GRB 080517 is dominated by a much older stellar population.…”
Section: The Host and Environment Of Grb 080517mentioning
confidence: 99%
See 1 more Smart Citation
“…Long-duration GRBs are typically associated with the peak light in their host galaxies, and with recent star formation (e.g Svensson et al 2010). However, the broadband continuum emission of the host of GRB 080517 is dominated by a much older stellar population.…”
Section: The Host and Environment Of Grb 080517mentioning
confidence: 99%
“…A number of studies now constrain the stellar properties of typical GRB hosts (e.g. Savaglio, Glazebrook, & LeBorgne 2009;Svensson et al 2010;Hjorth et al 2012), their radio properties (e.g. Micha lowski et al 2012;Stanway, Davies, & Levan 2010;Stanway, Levan, & Davies 2014;Perley et al 2014) and behaviour in the far-infrared (Hunt et al 2014;Symeonidis et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Those objects are typically relatively high mass, evolved systems. Zafar et al (2011) showed in an analysis of GRB afterglows that GRB host galaxies, which are typically young and star-forming with low metallicities and hard radiation environments (Christensen et al 2004;Castro Cerón et al 2006;Savaglio et al 2009;Svensson et al 2010;Chary et al 2002;Fynbo et al 2008;Watson et al 2010), have substantially lower dust-to-gas ratios than the local group even after accounting for metallicity.…”
Section: Extragalactic Metals-to-dust Ratiosmentioning
confidence: 99%
“…This underlying excess has been explained for many different reasons ranging from observational biases (Coward et al 2008;Elliott et al 2012) to redshift-dependent initial mass functions (IMF; Wang & Dai 2011). However, the most favoured explanation is a metallicity dependence that is driven by (i) the requirement of the single progenitor collapsar model, and (ii) LGRB host galaxy observations (see, e.g., Le Floc'h et al 2003;Savaglio, Glazebrook & Le Borgne 2009;Svensson et al 2010;Mannucci, Salvaterra & Campisi 2011).…”
Section: Manymentioning
confidence: 99%